Effectiveness and acceptance of Vestibulo-Ocular Reflex adaptation training in children with recurrent vertigo with unilateral vestibular dysfunction and normal balance function - Ma, Ning; Liu, Handi; Liu, Bing; Zhang, Li; Li, Bei; Yang, Yang; Liu, Wei; Chen, Min; Shao, Jianbo; Zhang, Xiao; Ni, Xin; Zhang, Jie (Frontiers in Neurology, 2022)
Objective: This was a block randomized controlled study to evaluate the effectiveness and acceptance of Vestibulo-Ocular Reflex(VOR) adaptation training in children with recurrent vertigo (RVC)with unilateral vestibular dysfunction (UVD) and normal balance function(NBF). Methods: Thirty children with RVC with UVD and NBF were analyzed. They were divided into three groups. Group A : VOR adaptation training, Group B :Cawthorne-Cooksey training, and Group C :no training.The Dizziness Handicap Inventory (DHI), Visual Analog Scale of Quality of Life with Vertigo (VAS-QLV), and canal paralysis (CP) on the caloric test were recorded before and after treatment. The Visual Analog Scale of Acceptance (VAS-A) was used to evaluate the acceptance of the training. Results: The effective rate was 100% in Group A, 65% in Group B, and 60% in Group C. The recovery rate on caloric testing was 100%, 70%, and 50%, respectively. Before and after training, DHI scores were 56.80±12.41/8.80±6.13 in Group A, 57.80±12.60 /18.80±9.72 in Group B, and 56.80±12.41/24.00±15.29 in Group C (all P=0.000). VAS-QLV scores were 7.50±0.97 /0.90 ±0.88 in Group A, 6.40±2.17/2.70±1.06 in Group B, and 6.60±1.58 /2.60±1.35 in Group C (P=0.000, P= 0.001, and P=0.000). The CP values were 35.70±15.09/12.90±8.06 in Group A, 33.60±20.11/23.6±19.28 in Group B, and 38.60±21.09/24.80±17.94 in Group C (P=0.001, P=0.367, and P=0.050) Each group comparisons showed that the decreases in DHI and VAS-QLV scores after training were significantly different (P=0.004, P=0.010), while CP values were not (P=0.399). In terms of acceptance, the VAS-A score was 7.60±2.17 in Group A and 3.10±2.77 in Group B（P =0.004）, The acceptance rate was 70% in group A and 10% in group B. Conclusion: For children with RVC with UVD but normal balance function, a single VOR adaptation program can effectively improve vertigo symptoms, and given its simplicity, time-effectiveness, and excellent outcomes, it is associated with better acceptance in children compared to classic Cawthorne-Cooksey training.